Mariátegui's Thought in the Peasant Struggles of Hugo Blanco. (July 2022) - Pensado Leglise, Patricia; Camacho Olvera, Nayeli
The peasant uprisings in the valleys of La Convención and Lares in Cuzco, Peru, in the late 1950s and early 1960s placed the Peruvian indigenous peasantry at the center of the national scene and led to the 1969 agrarian reform that would transform the property-labor system in the Peruvian countryside (a system that produced the famous Mariátegui aphorism "The problem of the Indian is the problem of land"). Hugo Blanco Galdós was an iconic figure and one of the leaders of this movement. Although Trotskyism was the most visible directive of his political praxis during his militancy in La Convención, the influence of José Carlos Mariátegui's (1894–1930) thought was what marked it. While the twenty-first-century indigenous peasant struggles have modified their objectives and discourse, Mariátegui's thought remains current in a figure such as Blanco. Los levantamientos campesinos en los valles de La Convención y Lares en Cuzco, Perú, a finales de la década de 1950 y principios de la década de 1960 pusieron al campesinado indígena peruano al centro de la escena nacional y condujeron a la reforma agraria de 1969, la cual transformaría el sistema de propiedad-trabajo en el campo peruano (sistema que dio lugar al famoso aforismo de José Carlos Mariátegui, "El problema del indio es el problema de la tierra"). Hugo Blanco Galdós fue una figura icónica y uno de los líderes de este movimiento. Aunque el trotskismo fue la directriz más visible de su praxis política durante su militancia en La Convención, la influencia del pensamiento de Mariátegui (1894–1930) fue lo que la marcó. Si bien las luchas campesinas indígenas del siglo XXI han modificado sus objetivos y discurso, el pensamiento de Mariátegui sigue vigente en una figura como Blanco.